Family – Appointed Factor of Religious Parenting - Tijūnėlienė, Ona (Acta Paedagogica Vilnensia, 2000)
The aim of this article is to discuss the terms and circumstances of the religious education of teenagers of Catholic and Orthodox faith in the family in the post-Soviet Klaipėda. The tasks are: to characterize pupil’s parents the attitude towards religion; to determine the agents of religious education of the pupils; to explain the beginning of the acquaintance of the teenager with the God; to discuss the role of religious holidays for the strengthening of the faith of a teenager. In 1998 the survey was carried out, 346 respondents took part, the pupils of the 7-9 classes. After the analysis of the results of the survey, the following conclusions were drawn: many pupils of 7-9 classes, who attend the lessons of religion, grow in religious families. This shows that the children choose worldview of their parents. A larger proportion of parents of the students of the Catholic school makes their children with the truths of faith known. The pupils of other schools were introduced to faith by their grandmothers. Pupils of all groups have the God met in different stages of their life, from early childhood to age 11-12. The current influence of parents on their children is not adequate with respect to quantitative expression of their religious feelings. Although in most families of both the religious groups religious holidays are celebrated, only over the half of the pupils experienced joy and other positive emotions. So, not all families have high culture of religious festivals and customs, and educational influence.
Keywords: Family; teenagers; religious education; Catholic; Orthodox.